Assessment of sedation level for endoscopic retrograde cholangiopancreatography – a prospective validation study. (4th March 2018) - Jokelainen, Jarno; Mustonen, Harri; Kylänpää, Leena; Udd, Marianne; Lindström, Outi; Pöyhiä, Reino
Abstract: Background and aims: There is no consensus on how to assess the depth of sedation for endoscopic retrograde cholangiopancreatography (ERCP). This study was carried out in order to evaluate different methods of assessment of depth of sedation: bispectral index (BiS), modified Richmond Agitation/Sedation Scale (mRASS), modified Ramsay Sedation Scale (mRSS) and modified Observer Assessment of Alertness and Sedation (mOAAS) and their applicability to clinical practice. Methods: Two hundred patients were recruited. Sedation was given by standard clinical practice using propofol sedation or patient controlled sedation. Sedation was assessed on all patients using the above-mentioned methods. BiS was considered the reference point for sedation scales. Cronbach's alpha was calculated to determine the consistency of different scales in respect to each other and prediction probability and Spearman's correlation coefficients of sedation scales were calculated to show the relationship between sedation scales and BiS. Results: All scales showed high reliability with overall Cronbach's alpha 0.943. Dropping scales suggested better consistency between mOAAS, mRSS and mRASS than with BiS. Spearman's correlation and prediction probability showed similar results with all tested scales: mOAAS (0.695, 0.739), mRSS (0.673, 0.735), mRASS (0.683, 0.738), p < .01 for all scales. Conclusions: All tested methods were found to be reliable in the assessment of the depth of sedation when compared with each other. However, mRASS, mRSS and mOAAS require the patient to respond to verbal or tactile stimulus, which may impair execution of ERCP, whereas BiS information is collected directly from electroencephalogram and thus may be preferable in clinical setting.